Narrative as resource for the display of self and identity: the narrative construction of an oppositional identity - Guerrero, Alba Lucy (Colombian Applied Linguistics Journal, 2011)
Narrative is a system of understanding that we use to construct and express meaning in our daily lives. The stories we narrate are not just resources for the development and presentation of the individual self; they allow us to see how identity is constructed within social and cultural worlds (Bruner, 1990). Schools and communities play a powerful role in shaping students identities; the ways in which stories are told and the identities they create are influenced by the environment in which they take place. In this paper, by using excerpts from a conversation I had with a High School student in an urban school in Bogotá, I will discuss how narrative analysis can be used to understand the way students construct their identities within their schools and communities. First, I will present the theoretical contexts linking narrative with self-construction. Next, I will discuss the methodological implications in the process of collecting and representing experiences highlighting the possibilities of narrative to make visible the construction of identities. Then pieces of a narrative told in a research interview will be analyzed illustrating different approaches of narrative analysis. The paper will conclude with a section that outlines the implications of using narrative in educational research.